Saving Paradise: A Culturally-Embedded GHRM Framework for Promoting Employee Sustainability in Bali’s Crisis-Hit Tourism Sector - Made, Arya Astina; Darma Putra , I Nyoman; I Ketut, Sutapa (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2025)
The rapid growth of Bali’s tourism industry—long admired as a tropical paradise—has created a sustainability paradox: while boosting economic development, it has simultaneously strained ecological resources and undermined cultural heritage. Existing Green Human Resource Management (GHRM) frameworks often overlook local values that are essential for sustainable practices in culturally embedded and crisis-sensitive island contexts. This study investigates how culturally grounded GHRM and Green Transformational Leadership (GTL), framed by the indigenous Tri Hita Karana philosophy, influence Employee Green Behaviour (EGB) and Environmental Performance (EP) in Bali’s tourism sector. Using a quantitative approach with data from 385 tourism employees, the model was tested through Partial Least Squares Structural Equation Modelling (SmartPLS 4.0). Results indicate that GHRM and GTL significantly affect both EGB and EP, with EGB serving as a partial mediator in both relationships. Cultural alignment significantly amplifies green behaviours and environmental performance. The study introduces a novel, culturally embedded GHRM framework that integrates leadership, HRM, and sustainability within the socio-spiritual context of Balinese tourism. Theoretically, it expands the application of green HRM by integrating indigenous philosophy; practically, it offers a scalable model for tourism-based economies seeking to harmonize economic, environmental, and cultural sustainability. While the cross-sectional, single-region design limits broader generalizability, this research provides a foundation for future comparative studies across culturally rich destinations.